PENGARUH PEMANFAATAN MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Andry Agustinus; Holilulloh Holilulloh; Hermi Yanzi (Jurnal Kultur Demokrasi, 2013)
The purpose of this study was to clarify the effect of the use of Media Images on learning outcomes of students of class VIII G on subjects Citizenship Education in SMP Negeri 1 Natarian South Lampung Academic Year 2012/2013. Principal  techniques  of  data  collection  using  questionnaire  and  supporting techniques  is to use the documentation. The  independent variable  in this  study  is the media  image,  while  the  dependent  variable  is  the  student  learning  outcomes. Based on  the  results  of  hypothesis  testing  showed  a  significant  relationship between the use of media images on the Grade VIII student learning outcomes G in  SMP  Negeri  1  Natarian  South  Lampung  Academic  Year  2012/2013.  This  is evidenced  by  the  results  of  calculations  using  Chi  square  formula  that  count  is greater  than  x2  x2  table,  (x2  ≥ x2 hit tab), which is 16.73 ≥ 9.49 at significant level  of  5%  (0.05)  and  a  significant  level  of  1%  (0.01)  obtained  x2  x2  count  is greater than the table, (x2 ≥ x2 hit tab), ie ≥ 13.3 16.73 with degrees of freedom = 4  ie  with  a  contingency  coefficient  of  0.55  and  contingent  Cmax  =  0.816  lies  in the closeness effect above 0.56 (high category). So that the results of such testing is  known  that  there  are  significant  utilization  of  media  images  of  the  class VIII  student  learning  outcomes  in  subjects  G  Citizenship  Education  in  SMP Negeri 1 Natarian South Lampung Academic Year 2012/2013.Tujuan penelitian ini adalah untuk menjelaskan pengaruh pemanfaatan media Gambar terhadap hasil belajar siswa kelas VIII G pada mata pelajaran Pendidikan Kewarganegaraan di SMP Negeri 1 Natar Lampung Selatan Tahun Pelajaran 2012/2013. Berdasarkan  hasil  pengujian  hipotesis  menunjukan  adanya  pengaruh  yang  signifikan  antara  pemanfaatan  media  gambar  terhadap  hasil  belajar  siswa  kelas  VIII G di SMP Negeri 1 Natar Lampung Selatan Tahun Pelajaran 2012/2013. Ini  dibuktikan  dengan  hasil  perhitungan  yang  menggunakan  rumus  Chi  kuadrat  bahwa x2 hitung lebih besar dari x2 tabel, (x2 hit ≥ x2 tab), yaitu 16,73 ≥ 9,49 pada  taraf signifikan 5% (0,05) dan taraf signifikan 1% (0,01) diperoleh x2 hitung lebih  besar dari x2 tabel, (x2 hit ≥ x2 tab), yaitu 16,73 ≥ 13,3 dengan derajat kebebasan = 4 yakni dengan kontigensi 0,55 dan koefisien kontigen Cmaks = 0,816 terletak pada keeratan  pengaruh  diatas  0,56  (kategori  tinggi).  Sehingga  dari  hasil  pengujian tersebut  diketahui  bahwa  terdapat  pengaruh  pemanfaatan  media  gambar  terhadap  hasil  belajar  siswa  kelas  VIII  G  pada  mata  pelajaran  Pendidikan Kewarganegaraan  di  SMP  Negeri  1  Natar Lampung  Selatan  Tahun  Pelajaran 2012/2013.Kata kunci : hasil belajar, pemanfaatan media gambar, pembelajaran kewarganegaraan